Application of Situational Leadership Style to Improve Teacher Performance at An-Nur Ibun Vocational School - Iman; Ujang Cepi Barlian; Hilya Anisa Sholihat Islamy; N Ela Nurlaela (al-Afkar, Journal For Islamic Studies, 2023)
Many factors influence the success of a school in achieving its educational goals, one of which is the leadership of the school principal. leadership is the process of influencing group activities within an organization to achieve goals. The method used in this study is a qualitative approach that is used to find out the reality of the events studied so as to make it easier to obtain objective data. Qualitative research is research that does not use calculations or is termed scientific research that emphasizes the natural characteristics of data sources. This research is descriptive in nature, only limited to an attempt to reveal a problem, situation or event as it relates to the problem of situational leadership style research in improving teacher performance at An-Nur Ibun Vocational High School. This study compares the data from the field with the library data in the form of theories and concepts that are relevant as assessment standards. The data that has been obtained through the results of observations, interviews, documentation studies. The findings obtained from the results of research at SMK An-Nur Ibun are as follows: 1) Application of the Instructive Leadership Style to Improve Teacher Performance, 2) Application of Consultation Leadership Style to Improve Teacher Performance, 3) Application of Participatory Leadership Style to Improve Teacher Performance, 4) Application of the Delegation Leadership Style to Improve Teacher Performance. Based on the results of research on situational leadership style to improve teacher performance at An-Nur Ibun Vocational High School, it can be concluded that the principal's situational leadership style is a picture of a flexible leader by providing a situation-based mechanism, in the sense that the principal has intelligence in reading situations and conditions. so that the principal understands when to tell, when to support, when to participate and when to delegate as well as leaders can act in a directive and supportive manner so as to improve teacher performance in an education. There are four situational leadership styles that affect the improvement of educator performance, namely the telling style, selling style, participating style and delegating style.